Teacher Performance and Learning Media Innovation: A Literature Review - Yansyah, Medi; Marian, Fungky; Utami, Ratna Tri (Journal Corner of Education, Linguistics, and Literature, 2025)
This study aimed to analyze the relationship between teacher performance and innovation in learning media and identify emerging research trends. Using the Systematic Literature Review (SLR) method, this study examines 500 articles from the Scopus database. It employs a bibliometric approach with VOSviewer to map concept relationships, publication patterns, and research gaps. The findings indicate that innovations in learning media, such as blended learning, digital technology, and interactive methods, significantly enhance teaching effectiveness and teacher motivation. Additionally, publication trends have shown a significant increase since 2019, reflecting growing academic interest in this topic, particularly in developed countries such as Spain, the United Kingdom, and the United States, as well as in developing nations like Indonesia and Malaysia. The main limitation of this study is that it exclusively relies on data from the Scopus database, thus excluding studies from other sources. Future research is recommended to explore the implementation of learning innovations in various educational contexts further and conduct a more in-depth analysis of the factors influencing their success.